Essentials of Mini ‒ One Anastomosis Gastric Bypass (Springer International Publishing, 2018)
This book indicates the technique and fine points of the mini- and one-anastomosis gastric bypass, and looks at the means of revising other operations related to it. The chapters discuss postoperative complications, treatment and requirements, postoperative diet and medications, the remarkable effects on the co-morbidities of morbid obesity, and the durability of the weight loss, as well as the improvement in the quality of life. Essentials of Mini ‒ One Anastomosis Gastric Bypass aims to help surgeons manage the difficulties encountered within this procedure and to help create improved practice.